New species of Gnathiidae (Crustacea, Isopoda, Cymothoida) from seamounts off northern New Zealand - Svavarsson, Jörundur (Zootaxa, 2006)
Gnathiid isopods collected from seamounts off northern New Zealand were examined. Two species of gnathiids were found, Caecognathia nieli sp. nov., and Gnathia sifae sp. nov. Caecognathia nieli sp. nov. is easily distinguished from all other known New Zealand gnathiid species in shape of the head, having an evenly rounded frontal border, and a fine bifid notch. Gnathia sifae sp. nov. is distinguished from all other New Zealand gnathiid species in having a distinct mediofrontal process on the cephalon, but no frontolateral processes. It is further clearly distinguished from the cooccurring species, Caecognathia nieli sp. nov., in having relatively larger eyes and of different shape, in the presence of lateral projections on the pereopods and in the shape of the appendix masculina.